PENGGUNAAN MODEL PEMBELAJARAN DIRECT INSTRUCTION UNTUK MENINGKATKAN KEDISIPLINAN SISWA PADA MATA PELAJARAN QUR’AN HADITS DI MTS SIROTHUL JANNAH MEKAR SEKUNTUM KECAMATAN TELUK KERAMAT - Rakuti Rakuti (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
Direct Instruction learning model to improve student discipline in Qur'an Hadith subjects at MTs Sirothul Jannah Mekar Sekuntum Teluk Keramat District for the 2019/2020 academic year, namely: a) Delivering Learning Objectives and preparing students; b) Prepare materials, namely materials that will be discussed in teaching and learning activities, c) Demonstrating knowledge and skills, d) Guiding training, e) Checking understanding and providing feedback, f) Providing training and application of concepts. From the efforts made by the Qur'an Hadith teachers, they can improve student discipline, especially in the implementation of learning or the learning process and are motivated to learn Qur'an Hadith subjects.